Effect of High-Efficiency Coagulant Formulations on Fluorine Wastewater Treatment Efficiency - Song Jirui; Min Jun; Wang Xiyuan; Zhang Lei (E3S Web of Conferences)
Fluorine wastewater is widely found in industries such as electronics manufacturing, electroplating, and aluminum processing, posing a serious threat to the ecological environment and human health. This study aims to evaluate the efficacy of high-efficiency coagulants of different formulations in enhancing fluorine wastewater treatment efficiency. CaCO3 was selected as the calcium source precipitant and three potential high-efficiency coagulants, polymerized aluminum chloride (PAC), polymerized aluminum ferric chloride (PAFC), and polyacrylamide (PAM), were screened for the comparative study. By conducting a series of laboratory-scale batch experiments, this study compared the effectiveness of these coagulants in treating fluorine wastewater under different dosages, pH, and reaction time conditions. The experimental results show that with CaCO3 as the calcium source precipitant, when the composite coagulant PAM was reacted for 32 min with a calcium-fluorine ratio of 0.7, pH adjusted to 5.8 and dosage of 1.6 g/L, it could efficiently remove fluoride ions from fluorine wastewater with a removal rate of more than 89%. Simultaneously, it made the pH close to neutral, which demonstrates its excellent performance of defluorination. This study provides important reference data for the improvement of the fluorine wastewater treatment process and offers a scientific basis for the selection of coagulants and optimization of operating parameters in practical application.